Effects of Foreign Presence in a Transition Economy: Regional and Industry-Wide Investments and Firm-Level Exports in Ukrainian Manufacturing - Stefan Lutz; Oleksandr Talavera; Sang-Min Park (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
We investigate the effects of regional and industry?wide foreign presence and foreign direct investment (FDI) on export volumes of Ukrainian manufacturing firms using unpublished panel data from 1996?2000. Foreign presence through FDI may have negative competition effects on domestic firms? performance while, at the same time, domestic firms? productivity may be increased by technology transfer or through training and demonstration effects. From a Cournot competition model including negative competition and positive technologyspillover effects, we derive the hypotheses that foreign presence and foreign investment might positively affect domestic firms? output and exports. Our estimation results support these hypotheses and suggest in particular that large firms and durable?goods producers benefit most from foreign presence and investments.
Keywords: F23; F14; L60; 330; transition; foreign direct investment; spillovers; firm performance